Workplace interpersonal conflict in prehospital emergency: Concept analysis - Mohammad Parvaresh-Masoud; Mohammad Ali Cheraghi; Masoomeh Imanipour (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: In the turbulent and stressful work environment of prehospital emergencies, the conflict among emergency medical technicians (EMT) and other health-care providers is inevitable. This study aims to examine the concept of workplace interpersonal conflict (WIC) in prehospital emergencies. MATERIALS AND METHODS: The eight-step Walker and Avant's concept analysis approach was adopted to define the concept. Iranmedex, SID, Magiran, ISC, PubMed, Scopus, Embase, and Web of Science searched with keywords such as WIC and hospital emergencies. After an extensive review of online national and international databases, one dictionary, nine books, and 25 articles in English and Persian were retrieved for the purposes of the study. RESULTS: The antecedents, attributes, and consequences of the concept identified. EMT must learn how to eliminate their destructive effects while enhancing constructive effects. CONCLUSION: Conflict is an inevitable part of life, and EMT must learn how to reduce their destructive effects while increasing constructive results.